Muhammad Al-Fatih's Conquest of Constantinople: Strategies and Implications - Dewi, Atika Sandra; Irham, M. Iqbal; Wanto, Sugeng (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
This research focuses on the expansionist policies pursued by Sultan Muhammad Al-Fatih and their impact on the regions surrounding Constantinople. The qualitative study aims to delve deeper into the strategies employed by Al-Fatih and contribute to a deeper understanding of his political expansion. The research methodology involves analyzing historical accounts and relevant literature, conducting a comprehensive review of existing scholarly works, and employing a descriptive analytical approach. The study highlights the military preparation, diplomacy and alliances, siege tactics, technological utilization, and post-conquest rule as key factors in Al-Fatih's expansionist endeavors. The conquest of Constantinople had significant ramifications for both Europe and the Islamic world. In Europe, it altered the political landscape, led to changes in trade routes, and resulted in massive migrations. In the Islamic world, it elevated the status and pride of the Muslim community, inspired other leaders, and influenced art, architecture, and literature.